Analysis of the experience of pedagogical support of military personnel in a military university - O. O. Nazarenko; L. V. Kotenko; S. V. Voznyi (Вестник Северо-Кавказского федерального университета)
Introduction. The relevance of the study is due to the results of the analysis, which allow characterizing the existing experience of pedagogical support for military personnel.Goal. The study aims to highlight the problems and prospects in the pedagogical support of military personnel associated with building up positive experience in this process, organized in the interests of training military specialists of the Armed Forces of the Russian Federation.Materials and methods. The study is based on the analysis of information sources confirming the organization of pedagogical support for military personnel in a military university (orders, instructions, recommendations, documents, etc.). To obtain reliable information necessary for a detailed study of the existing data, empirical and theoretical methods were used (analysis, observation, study of experience, conversations, testing, survey, generalization, systematization, etc.).Results and discussion. The results of the analysis of the experience of pedagogical support of military personnel of a military university showed that the main part of it is devoted to advisory activities on the organization of research work in the interests of the Eighth Directorate of the General Staff of the Armed Forces of the Russian Federation. It should be said that the professional training of information security specialists in military universities has always attracted the attention of scientists, as well as their pedagogical support, which functionally ingrates into training, as a technology for solving problems in order to develop new personnel, including operators of a scientific company. Accordingly, the multilevel integrated dynamic personal and professional development of military personnel – operators of a scientific company, characterized by the presence of a stable structure of value orientations that determine the nature of professional activity in terms of information protection, became subject to analysis.Conclusion. Based on the results of the study, it can be concluded that the need to integrate pedagogical science into the militarytechnical educational sphere is subject to discussion, as the main link for managed and regulated activities that ensure the personal and professional development of military personnel in a specific field of activity